IMPLEMENTASI STRATEGI PEMBELAJARAN KONTEKSTUAL DI MI (MADRASAH IBTIDAIYAH) - Much. Machfud Arif; Rr. Kusuma Dwi Nur Ma'rifati (Program Studi PGMI Fakultas Tarbiyah Institut Agama Islam Nahdlatul Ulama Tuban, 2019)
Learning is essentially a process of interaction between students and their environment, so there is a change in behavior to be better. In learning, the most important task of the teacher is to condition the environment so that it supports behavior change for students. The use of appropriate learning strategies will also determine the effectiveness and efficiency of learning. Learning needs to be done with fewer lectures and teacher-centered methods, and more emphasis on student interaction. The use of a variety of strategies will greatly assist students in achieving learning objectives. One good learning strategy is contextual learning strategy. Because contextual learning strategies can combine three aspects of intelligence, including cognitive, affective and psychomotor aspects. Contextual learning strategies can provide space for students to be directly involved in the learning process. So students are no longer seen as objects, but subjects who can show their existence and contribution in education. Contextual learning and teaching involve students in important activities that help them relate academic learning and the real life contexts they face. By linking the two, students see the meaning in schoolwork. Fiqh subjects in madrasah ibtidaiyah with a contextual learning strategy approach provide opportunities for students to explore cognitive abilities in implementing material in the process of teaching and learning activities more innovative and comprehensive.